Ensemble classics for brass quartet Book I For two Bb cornets, horn in F and trombone or baritone - VOXMAN, H. (Rubank Inc., 1947)
As torrents in summernAutum songnCelebration of springnChoralenChorus of the peasantsnDivine praise